Isolation of cDNA clones coding for rat tyrosine aminotransferase. - Scherer, G (1982)
Tyrosine aminotransferase (TyrATase; L-tyrosine: 2-oxoglutarate aminotransferase, EC 2.6.1.5) from rat liver is subject to glucocorticoid and cAMP as well as developmental control. To isolate DNA sequences encoding TyrATase, we constructed a cDNA library from rat liver poly(A)+RNA enriched for TyrATase mRNA. Recombinant plasmids were screened by differential colony hybridization to poly(A)+RNA isolated from adrenalectomized and dexamethasone-treated animals. Differentially hybridizing plasmids were then shown to contain TyrATase cDNA sequences by their ability to select a mRNA whose in vitro translation product is immunoprecipitable with antiserum against TyrATase. In confirmation, we detect mRNA homologous to TyrATase cDNA sequences in hepatoma cell lines known to contain TyrATase activity but not in a cell line lacking this activity. We show that treatment of rats with dexamethasone or N6,O2'-dibutyryladenosine 3',5'-cyclic monophosphate leads to a 5- to 10-fold increase in the amount of TyrATase mRNA.